The Types and Motives of Maxim Infringement in Agatha Christie’s Murder on The Orient Express Novel (Pragmatic Approach) - darmawan, Adhitya; Nada Humaida Rohmah, (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This study performs a pragmatic analysis of Agatha Christie’s "Murder on the Orient Express," focusing on the intentional types and motives behind Grice’s conversational maxims infringement strategies. This research is descriptive qualitative that uses document analysis from the dialogues where the characters strategically infringe the maxims and find the motive(s) behind every infringement. The motives are namely withholding information, providing misleading details, using ambiguity, and creating communicative effects. This research uses domain, taxonomy, componential analysis, and cultural theme as well as inductive technique for the data analysis technique. The results show that there are 118 infringements of the maxims that fulfill the types of all the maxim of quality, quantity, manner, and relevance as well as the motives This research finds out that the story is dominated by the infringement of the maxim of relevance to control information flow which aligns with the novel’s purpose as a crime-solving detective novel.